Seismic Performance Evaluation of Simple Reinforced Masonry Houses with Brick Walls: Experimental and Numerical Approaches - Pasya, Namira Risza; Saputra, Ashar; Setiawan, Angga Fajar; Priyosulistyo, Henricus (ASTONJADRO, 2025)
This study aims to evaluate the performance of brick houses against earthquakes through experimental and numerical approaches. The research objects include two single-story houses located at University of Gadjah Mada (UGM) and Turi, Sleman, Yogyakarta. Microtremor measurement was carried out using accelerometers to record building vibrations, which were then analyzed using Fast Fourier Transform (FFT) to obtain the natural frequency on site of the structure. Numerical modeling was carried out using finite element analysis to validate and asses the building’s frequency response to earthquake loads based on Service Level Earthquake (SLE), Design Basis Earthquake (DBE), and Maximum Considered Earthquake (MCE). The results of the study indicate that the modeling can be validated based on the natural frequency approach from field and numerical evaluate. The maximum displacement that occured at the SLE, DBE, and MCE levels exceeded the allowable limits, indicating that both houses are in an unsafe condition. The structural performance evaluation based on Federal Emergency Management Agency (FEMA 356) shows that the houses in UGM and Turi fall into the Collapse Prevention (CP) category, which mean that the building can no longer be used as houses on the verge of collapse. Although the maximum acceleration analysis of the houses indicates that the values are lower than the design peak ground acceleration (PGAM), structural failure may still occur. The results of this study are expected to provide insights into earthquake-resistant house design as well as recommendations for improving structural resistance to seismic load.